Insects and Public Health - Claret D’Souza; V. Basil Hans (International Journal of Insects, 2025)
Insects have two roles in public health: they can spread disease and help with health treatments. This article looks at the complicated relationship between insects and public health, with a focus on how they spread diseases including malaria, dengue, Zika, and Lyme disease. The ecology, behaviour, and distribution of important vector species are looked at along with the social and environmental elements that cause outbreaks. The article also talks about how more and more people are interested in how insects might be used for good, including in sustainable food systems, waste management, and even medical treatments. There is talk about public health tactics for vector management, surveillance, and getting people involved in the community. These strategies stress the need for integrated, interdisciplinary approaches. As climate change and urbanisation transform insect populations all over the world, it is more important than ever to understand how they affect human health. This review emphasises the necessity for ongoing research and innovation in the management of the hazards and advantages that insects present to public health.
Keywords: Climate change and the spread of diseases; and vector control; insect ecology; public health monitoring; vector-borne diseases